Analisis Penanganan Pembiayaan Mikro Dengan Akad Murabahah Pada Nasabah Yang Meninggal Dunia Sebelum Jatuh Tempo - Marcellina, Silvia; Sulaeman, Sulaeman (Universitas Dian Nuswantoro, 2023)
The purpose of this study was to find out how to handle microfinance with murabahah contracts for customers who died before maturity. This research was conducted using a qualitative method with a descriptive approach. The data collection method that the author uses is the method of observation, interviews, documentation and triangulation related to microfinance with murabahah contracts at Bank Syariah Surade Branch Offices. Based on research results. Handling is carried out for cases of customers who die before maturity, namely by claiming life insurance at insurance institutions and freeing heirs who have payment obligations in installments.